Oceanographic Buoys for Marine Monitoring: A Review of Instrumentation, Applications, and Emerging Technologies - Francisco Portillo; Nadia Rotbi; Nicolas Padilla; Consolacion Gil; John Alexander Taborda; Alfredo Alcayde; Maria Isabel Saez (Journal of Marine Science and Engineering, 2026)
Oceanographic buoys are essential platforms for marine observation, supporting real-time monitoring, climate studies, operational oceanography, coastal management, and offshore activities. This review maps the scientific literature on oceanographic buoys and identifies the main research sectors that structure the field. A Scopus search using TITLE-ABS-KEY((oceanographic OR metocean OR “ocean observing” OR “ocean observation”) AND (buoy OR buoys)) retrieved 1876 documents published between 1938 and 2026. The records were processed using a network-based sector detection and visualization workflow. Five thematic sectors were identified: platform engineering, sensors, moorings, and autonomous systems; marine wind, waves, metocean, and offshore energy applications; physical oceanography, sea-surface temperature (SST), currents, and environmental variability; coastal and ocean observing networks and operational services; and drifting buoys, floats, and global ocean datasets. The results show that buoy research has evolved from isolated measurement systems to integrated observing infrastructures that combine in situ sensing, satellite validation, autonomous operation, telemetry, and decision-support services. By linking bibliometric structure and thematic interpretation, this review provides a sector-based map showing where scientific observation, engineering design, operational services, and autonomous technologies converge.

Postbiotics for the management of obesity, insulin resistance/type 2 diabetes and NAFLD. Beyond microbial viability - Laura Isabel Arellano-García; María P. Portillo; J. Alfredo Martínez; Arnaud Courtois; Iñaki Milton-Laskibar (Critical Reviews in Food Science and Nutrition, 2025)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Participation and detection rates by age and sex for colonoscopy versus fecal immunochemical testing in colorectal cancer screening - Dolores Salas; Mercedes Vanaclocha; Josefa Ibáñez; Ana Molina-Barceló; Vicente Hernández; Joaquín Cubiella; Raquel Zubizarreta; Montserrat Andreu; Cristina Hernández; Francisco Pérez-Riquelme; José Cruzado; Fernando Carballo; et al. (Cancer Causes & Control, 2014)

Assessment of genetic fidelity among Agave tequilana plants propagated asexually via rhizomes versus in vitro culture - Martha Isabel Torres-Morán; Martha Escoto-Delgadillo; Sandy Molina-Moret; Diana M. Rivera-Rodríguez; Ana P. Velasco-Ramírez; Diógenes Infante; Liberato Portillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)